Menumbuhkan Semangat Wirausaha Bagi Masyarakat Berbasis Pengolahan Hasil Pertanian Di Desa Ketangga Kecamatan Suela Lombok Timur - Wahyunadi; Agustiawan, Adil; Wulandari, Irma; Wasa, Margareth Aurelia (Universitas Mataram, 2024)
Abstrak – Kuliah Kerja Nyata (KKN) is one of the community service activities to fulfil the Tri Dharma of Higher Education. Kuliah Kerja Nyata (KKN) Group at the University of Mataram in Loloan Village for the 2022/2023 period carried out community service activities with the theme of Advanced and Sustainable Agriculture. Drip irrigation is one of the more efficient land irrigation technologies. The application of drip irrigation is one way to realize advanced and sustainable agriculture. The purpose of this work program is to provide agricultural extension efforts to convience farmer groups to use drip irrigation technology in Loloan Village, Bayan District, North Lombok Regency from December 2022 to February 2023. The efficiency level of water use on agricultural land should be optimized by implementing use of appropriate irrigation techniques. Agricultural extension effort in apllying drip irrigation technology used include : dissemination of drip irrigation technology, procedures for using drip irrigation, application of drip irrigation, and the obstacles encountered in the process of applying drip irrigation equipment such as drip hoses. This drip irrigation technique is expected to help farmers save water use on plants and save time because watering is done automatically. So, that it can increase the utilization of nutrients in the soil, accelerate plants seeds to adapt, and also increase the success of these plant to grow. Key Words : Agriculture, Drip Irrigation, Land Irrigation